SURAU MELALUI BAHASA TUBUH DALAM FILM EKSPERIMENTAL - Deddy Desmal (Tamaddun, 2018)
AbstractMinangkabau has a surau as a creative container for its people to worship, study, play, exchange ideas and share experiences in ancient times. The existence of the surau is the biggest scourge of Islamic civilization in Minangkabau. Surau became the medium of educational activity of Muslims and the place of all social activities in Minangkabau. Humans communicate with other humans using direct communication (dialogue) and indirect communication (body language). Body language in general is nonverbal message communication (without words). Body language becomes an alternative way to communicate using body language or sign language. Experimental films are abstract and not easy to understand. This is because the filmmaker uses personal symbols in his speech. Structures in experimental films by subjective interpretations of the work such as ideas, ideas, emotions and inner experiences.